Serious Game Promotes the Cultural Transmission of Agricultural Heritage Mulberry-Dyke and Fishpond System - Ning Gao; Buchao Wang; Xinheng Pan; Lan Yang; Shijie Tan; Xuguang Zhu (SAGE Open)
The Zhejiang Huzhou Mulberry Base Pond System (HMBPS) is a complex and comprehensive “Globally Important Agricultural Heritage System (GIAHS).” Current research on the conservation of HMBPS predominantly focuses on agriculture, ecology, and land management, while the studies addressing socio-cultural aspects are notably lagging behind, which challenges the preservation of HMBPS. The study of the modernization and dissemination of the HMBPS is of great significance to the preservation and transmission of GIAHS. This paper presents the development of a digital serious game titled “Mulberry Base Pond System World (MBPS),” utilizing the GPS game development model. The game simulates the system elements, characteristics, and operational logic of the HMBPS. Students are invited to use this digital serious game. In this process, we assessed the effects of digital serious game on respondents’ cognitive level, cognitive structure, and interest in learning about HMBPS culture through pre-tests, post-tests, game assessment questionnaires, and semi-structured interviews. The results of the experiment show that the digital serious game improve respondents’ understanding and learning interest in the HMBPS, as well as foster the formation of a positive learning style. In addition, the digital serious game can help respondents better understand how the agricultural system works. Furthermore, combining serious digital games with educational tourism, increasing the interaction between real and virtual environments, developing multiplayer “cooperative games,” could be potential directions to promote cultural dissemination of agricultural heritage.